A Review of Sensory Imagery for Consumer Psychology - Elder, Ryan S.; Krishna, Aradhna (Journal of Consumer Psychology, 2022)
This review of mental imagery research has the core objective of fostering more research on the topic of sensory imagery. The review is organized around a conceptual framework highlighting (a) how mental imagery is formed, (b) the elicitation and elaboration of mental imagery, (c) the multi‐modal nature of sensory imagery, and (d) the consumer behavior consequences of mental imagery. This conceptual framework provides many new lenses through which researchers can view prior findings, and thereby motivates innovative new research ideas. Future research directions are provided in each section of the review, with additional unexplored opportunities presented in a final section.